Neoliberal politics in Latin America and investment in public-private partnerships for infrastructure - Vásconez Cruz, José Emilio (2019)
This research aims to understand the differences in the application of public-private partnerships (PPP) for investment in infrastructure in 16 Latin American countries during the last seventeen years. For this end, a variable called “social memory of neoliberalism” is applied to determine the impact of neoliberalism in the creation of public-private partnerships in the region. Three indicators were used to measure the memory of neoliberalism and infrastructure: public opinion on privatization, level of privatization during neoliberalism, and the position of the currentgovernment toward neoliberalism. After processing the data obtained, descriptive statistics was used to compare the three indicators with the level of public-private partnerships in each country. The results demonstrate that the social memory of neoliberalism influences the countries in different ways for the generation of PPPs. Additionally, they show that in some countries neoliberal social memory has a direct impact on public-private investment for infrastructure.